Thermal performance of energy pile with deeply penetrating 1-U-shape heat exchanger. (March 2021) - Lyu, Weidong; Pu, Hefu; Xiao, Henglin; Hu, Dawei; Ma, Qiang
Highlights: Deeply penetrating 1-U-shape heat exchanger configuration is proposed. The proposed configuration can yield up to 122 % increase in heat transfer. Thermal performance is optimal when the ratio of tube depth to pile length is 2.25. Raising inlet water temperature from 35 to 50 °C gives 90 % heat transfer increase. Doubling flow rate from 0.342 to 0.684 m 3 /h yields 11 % increase in heat transfer. Abstract: This study presents a novel heat exchanger configuration for energy pile, which is called the deeply penetrating 1-U-shape configuration. Heat transfer performance of energy pile with the proposed configuration is compared with the traditional 1-U-shape and 1-W-shape configurations to demonstrate its superior heat exchange efficiency. Parametric analysis is performed to investigate the effects of several important parameters (i.e., ratio of tube depth to pile length, tube diameter, inlet water temperature, and water flow rate) on the heat transfer performance. Simulation results indicate that a ratio of tube depth to pile length around 2.25 yields the optimal heat transfer performance.